Labor Economics and Sociology of Labor: Demarkation Problem - S N Lebedev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2011)
The article deals with important economic and sociological problems taking into account their relevance to economics and sociology of labor as two independent sciences. The author suggests some demarcation boundaries of the concepts relevant to contemporary life within these two disciplines.